AKIBAT HUKUM TERHADAP PENJUALAN GAS ELPIJI 3 KG DI ATAS HARGA ECERAN TERTINGGI (HET) DI WILAYAH KOTA PEKANBARU - M. Arbi Ubaidillah; Mardalena Hanifah; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Based on the Decree No. 430 Pekanbaru Mayor of the Year 2015 Adjustments second highest retail price of Liquefied Petroleum Gas Tubes 3 Kg Subsidized in Pekanbaru, that the price per 3 kg LPG cylinder is Rp. 18,000 (eighteen thousand rupiah). But the facts found is still the number 3 kg LPG gas stations that sell above the highest retail price set by the government. From this background, the authors conducted a study titled "Effects of 3 Kg LPG Gas Sales Above the highest retail price (HET) in Pekanbaru City Region".The issues that the authors made the basis of this research is how the legal consequences of the sale of LPG 3 kg above the highest retail price (HET) in the city of Pekanbaru and how the government's attempt to impose the highest retail price (HET) LPG 3 kg in accordance with government regulations Pekanbaru. While the purpose of writing, among others to determine the legal consequences of the sale of LPG 3 kg above the highest retail price (HET) in the city of Pekanbaru and to know the government's attempt to impose the highest retail price (HET) LPG 3 kg in accordance with government regulations Pekanbaru.This type of research can be classified in this type of empirical legal research or sociological, because in this study the authors directly conduct research on the location or point examined in order to provide a complete and clear picture of the issues examined. This research was conducted at the Department of Industry and Trade as well as at several bases Pekanbaru 3-kg LPG in the urban area of Pekanbaru involved in the problems studied. Source of data used, namely: primary data and secondary data. Data collection techniques in this study using observation, interviews, and review of the literature.The results obtained from are the First, implementation of sales gas LPG 3 kg was not effective due to the persistence of the bases that sell gas LPG 3 kg above of the highest retail price (HET) which has been established by the City of Pekanbaru in accordance with the Decree of the Mayor of Pekanbaru No. 430 2015 adjustments second highest retail price of Liquefied Petroleum gas tubes 3 Kg Subsidized in Pekanbaru, that the price per LPG cylinder is Rp. 18,000 (eighteen thousand rupiah); Second, efforts to overcome obstacles in violation of the highest retail price (HET) is a need for synergy and cooperation relationship between the City Government with Pertamina; Installation information highest retail price (HET) LPG 3 kg at each base and the provision of strict sanctions by the Department of Industry and Trade of the base abuse; Department of Trade and Industry should actively seek information regarding daily stall not base that sell LPG 3 kg; and the distribution uneven base, especially for areas located some distance away from the agency.Key words: Retail Price, Propane, Sales